(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper delves into the captivating realm of women’s voices and identity within the literary works of two distinguished Indian authors, Namita Gokhale and Anita Desai. The exploration of their novels reveals a rich tapestry of female characters and narratives that encapsulate the multifaceted experiences of women in Indian society